Artistic conventionality in painting - Basanets Luka; Maslova Tetiana (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2021)
Article addresses the theoretical meaning of artistic conventionality. Its fundamental role in painting is undeniable and is to be not only familiarised with, but also studied thoroughly. The mastering of a complex and voluminous morphology of artistic conventionality alongside the lack of literature sources concerning its features in the visual arts, in particular in painting, which is the main object of our attention, are laborious parts of this process. The article: a) proposes the introduction of three steps in the study of conventionality at the initial stages of training with a detailed description of the general provisions on artistic conventionality, in order to ensure a conflict-free process of mastering a complex body of knowledge in the future; b) provides selection of the information from its total amount concerning the artistic conventionality in fine arts, emphasising its presence in painting. The article realises the intention to supplement the information on artistic conventionality with the analysis of the class and genre indicators of painting. The systematic study of artistic conventionality is becoming a factual way enabling us to enrich the level of professional literacy of students - future teachers and practising artists.